2020
DOI: 10.3390/antibiotics9120853
|View full text |Cite
|
Sign up to set email alerts
|

Silver Antibacterial Synergism Activities with Eight Other Metal(loid)-Based Antimicrobials against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus

Abstract: The present study surveys potential antibacterial synergism effects of silver nitrate with eight other metal or metalloid-based antimicrobials (MBAs), including silver nitrate, copper (II) sulfate, gallium (III) nitrate, nickel sulfate, hydrogen tetrachloroaurate (III) trihydrate (gold), aluminum sulfate, sodium selenite, potassium tellurite, and zinc sulfate. Bacteriostatic and bactericidal susceptibility testing explored antibacterial synergism potency of 5760 combinations of MBAs against three bacteria (Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…As found previously 32 34 , differences in antimicrobial susceptibility towards metal-based antimicrobials is seen between the three different strains. The strains chosen for evaluation include a Gram-negative enteric pathogen Escherichia coli, the opportunistic pathogen and ubiquitous soil organism Pseudomonas aeruginosa and the Gram-positive opportunistic pathogen Staphylococcus aureus .…”
Section: Antimicrobial Assayssupporting
confidence: 83%
“…As found previously 32 34 , differences in antimicrobial susceptibility towards metal-based antimicrobials is seen between the three different strains. The strains chosen for evaluation include a Gram-negative enteric pathogen Escherichia coli, the opportunistic pathogen and ubiquitous soil organism Pseudomonas aeruginosa and the Gram-positive opportunistic pathogen Staphylococcus aureus .…”
Section: Antimicrobial Assayssupporting
confidence: 83%
“…This sterilization mechanism has been reported by Fonseca et al [ 41 ], and the sterilization effect of our composites is better than theirs. It can also be seen in Figure 13 that the bactericidal effect of TiO 2 /PLA composites is weaker than that of the coating on this basis, since the silver particles on the surface of the coating can be tightly combined with the sulfhydryl group of the enzyme protein in the bacteria to make the protein coagulate, destroying the activity of cell synthase, and causing the cell to lose the ability to divide and die [ 42 , 43 ]. Another important reason is that the TiO 2 content of the coating is more than that of the composites under the same surface area.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the combination of multiple antibacterial agents to achieve enhanced antibacterial effects has become a research hotspot (Pormohammad & Turner, 2020). With the excessive use of antibiotics and metal ions, bacteria gradually acquire drug resistance through horizontal gene transmission or gene mutation (Sutterlin et al, 2017).…”
Section: Synergistic Antimicrobial Effects Between Gallium and Other ...mentioning
confidence: 99%
“…Several studies investigated the antimicrobial synergies between different metal ions, and fractional inhibitory concentration and fractional bactericidal concentration assays were used to evaluate synergistic intensity (Yoon et al, 2006;Aziz, 2019;Vaidya et al, 2019;Pormohammad & Turner, 2020). The results showed that silver ions, zinc ions, Cd, Se, and Ga had good synergistic effects.…”
Section: Synergistic Antimicrobial Effects Between Gallium and Other ...mentioning
confidence: 99%